2005
DOI: 10.1063/1.1954890
|View full text |Cite
|
Sign up to set email alerts
|

Resonant excitation of plasma oscillations in a partially gated two-dimensional electron layer

Abstract: We have solved the problem of diffraction of terahertz radiation on a perfectly conductive gate strip that partially screens a two-dimensional (2D) electron layer located at some distance from the gate. Scattering and absorption spectra of such a structure reveal the fundamental plasma resonance excited under the gate. We have shown that the absorption enhancement factor at plasma resonance may reach very high values (up to 60). However, for narrow gate strips (with the width less than 100nm) the resonant scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 11 publications
2
48
0
Order By: Relevance
“…Two dimensional (2D) THz plasmons in silicon (Si) [4], III-V materials such as GaAs/AlGaAs [5] and GaN/AlGaN [6] heterostructures, and graphene [7,8] similarly are sub-wavelength compared to free-space electromagnetic waves, but have an additional degree of freedom due to the ability to control electron density, and thus the 2D plasma frequency, through a field effect. It is this latter capability that has generated interest in 2D plasmonic devices [9,10] such as THz detectors [11][12][13][14], mixers [15,16], emitters [17,18], and field enhancement structures [19].…”
mentioning
confidence: 99%
“…Two dimensional (2D) THz plasmons in silicon (Si) [4], III-V materials such as GaAs/AlGaAs [5] and GaN/AlGaN [6] heterostructures, and graphene [7,8] similarly are sub-wavelength compared to free-space electromagnetic waves, but have an additional degree of freedom due to the ability to control electron density, and thus the 2D plasma frequency, through a field effect. It is this latter capability that has generated interest in 2D plasmonic devices [9,10] such as THz detectors [11][12][13][14], mixers [15,16], emitters [17,18], and field enhancement structures [19].…”
mentioning
confidence: 99%
“…Two main hypotheses on the origin of an additional broadening are currently under consideration: l existence of oblique plasma modes [19,20], l additional damping due to the leakage of gated plasmons to ungated parts of the transistor channel [21]. The first hypothesis is related to the fact that in realistic devices the gate width is much greater than the gate length.…”
Section: Thz Detection By Gaas and Ingaas Fetsmentioning
confidence: 99%
“…Therefore, the plasma under the gate cannot be treated independently of the plasma in ungated parts. An interaction between the two plasma regions can lead not only to a modification of the resonant frequency [19,21], but also to line broadening. To decrease the role of oblique modes, one has to change the geometry of the channel.…”
Section: Thz Detection By Gaas and Ingaas Fetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling mechanism between 2D plasmons and external electromagnetic waves were discussed in [4][5][6][7]. It was suggested that this coupling might be stronger using the design of field effect transistors array with grating gates [8].…”
Section: Introductionmentioning
confidence: 99%